Multidirectional percutaneous drilling and autologous bone marrow injection for the treatment of femoral diaphyseal nonunions: a prospective interventional study - Li M; Meng Y; Li Y; Long A; Lv H; Yin P; Zhang L; Tang P (Therapeutics and Clinical Risk Management, 2019)
Ming Li,1,* Yutong Meng,2,* Yi Li,1 Anhua Long,3 Houchen Lv,1 Pengbin Yin,1 Licheng Zhang,1 Peifu Tang11Department of Orthopaedics, Chinese PLA General Hospital, Beijing 100853, People’s Republic of China; 2Department of Orthopedics, Beijing Chaoyang Hospital, Capital Medical University, Beijing 100020, People’s Republic of China; 3Department of Orthopaedics, Beijing Luhe Hospital, Capital Medical University, Beijing 101100, People’s Republic of China;Correspondence: Peifu Tang; Licheng ZhangDepartment of Orthopedics, Chinese PLA General Hospital, No.28 Fuxing Road, Haidian District, Beijing 100853, People’s Republic of ChinaTel +86 10 6821 2342Email pftang301@163.com pftang301@163.com*These authors contributed equally to this workBackground: To examine the outcomes of multidirectional percutaneous drilling and autologous concentrated bone marrow (BM) transplantation for atrophic femoral diaphyseal nonunion characterized by intact hardware and mechanical stability at the nonunion site.Methods: Fourteen patients (22–63 years of age) were admitted to our hospital with atrophic femoral diaphyseal nonunion. All patients were treated with a combination of multidirectional percutaneous drilling and autologous concentrated BM transplantation. Radiographic evaluation was conducted every month after transplantation until bone healing was achieved.Results: Bony union was achieved in 13 of the 14 patients (92.9%) after an average of 3.9 months (range: 2.5–6 months). The average radiographic union scale in tibial (RUST) scale score improved significantly from the preoperative period (6.15±1.21) to follow-up (11.23±0.73; P<0.05). The mean follow-up after transplantation was 31.4±9.5 months (range: 18–50 months). At the final follow-up, the quality of function had improved significantly, allowing a return to normal activities.Conclusion: Combined multidirectional percutaneous drilling and autologous concentrated BM transplantation is an easy, safe, inexpensive, and efficacious method to treat atrophic femoral diaphyseal nonunion characterized by intact hardware and mechanical stability at the nonunion site.Trial registration number: ISRCTN29808592Keywords: autologous bone marrow injection, multidirectional percutaneous drilling, femoral diaphyseal fracture, nonunion